KAJIAN TENTANG SISTEM PENGINGAT LOKASI PINTU AKSES MALL BERBASIS PENGENALAN LOGO OUTLET - Erwin Erwin; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Mall have a lot of access to the parking lot, which can leads visitor of the mall to forget where they park their car and how to get there. This paper presents a system to tackle this problem by logo recognition using a modified method, Modified Line Segment Hausdorff Distance (MLHD). The system takes image of a shop with the shop logo, captured so that the shop logo is on the top of the image as input.  The system cuts the top area of the image, where the shop logo supposed to be, and do the preprocessing which consist of edge detection using Canny and thinning using Zhang-Suen method before recognize the shop logo using MLHD.